Corrigendum Candidate Gene Locus for PHACE Syndrome. Am J Med Genet A. 2012;158(6):1363–1367. Doi:10.1002/ajmg.a.35341 (American Journal of Medical Genetics Part A, 2022)
Beckwith-Wiedemann spectrum (BWSp) is an overgrowth disorder characterized by its main clinical features macrosomia, macroglossia, and abdominal wall defects. BWSp is caused by (epi)genetic chromosome 11p15 alterations with approximately 20%-27% of patients exhibiting mosaic paternal uniparental disomy of chromosome 11p15 (pUPD11p15). In this study, we analyzed 46 newly identified patients with pUPD11p15. We investigated the ratio of mosaicism and the extent of pUPD11(p15) segment length and explored their correlation with the clinical phenotype. Additionally we compared the cardinal and suggestive features of our cohort with previously reported pUPD11p15 patients in the literature. The most common phenotypes in our cohort were lateralized overgrowth, organomegaly and macroglossia. While no correlation was found between the segment length and clinical phenotype, a significant positive correlation was observed between the BWSp clinical score and mosaic ratio in blood. This correlation was primarily driven by macroglossia. In contrast to previously published studies reporting mosaic genome-wide paternal UPD (MGWpUPD) in 2%-19% of patients with pUPD11 and BWSp, this was not detected in our cohort.